Предмет: Алгебра,
автор: 0Лида0
Упростите выражение (2z + 3)2 – (2z + 1)(4z + 3) – 2z
и найдите его значение при z = –2.
ПОМОГИТЕ, ПЛЕС, А ТО ТУПЛЮ :з
Ответы
Автор ответа:
0
4z+6-8z^2-6z-4z-3-2z=-8z^2-8z+3
если z=-2,то -8*(-2)^2-8*(-2)+3=-24+16+3=-5
если z=-2,то -8*(-2)^2-8*(-2)+3=-24+16+3=-5
Похожие вопросы
Предмет: Алгебра,
автор: Ymnuk56
Предмет: Алгебра,
автор: telefon100120
Предмет: Математика,
автор: 2011ZHANARA
Предмет: Математика,
автор: ТанюшаЭлис
Предмет: Математика,
автор: Человек56666